Analisis Strategi Pemasaran Ternak Berbasis E-Commerce di PT X - Aprilia, L.; Cyrilla, L.; Burhanuddin, Burhanuddin (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2018)
PT X is one of the online livestock marketplace companies that connects partners (housing investors, business partners, members, and farmers) with consumers. Products that were marketed by PT X include sheep (gembel, garut, merino) and cow (ongol, hisar, simmental). PT X in marketing its products used online marketing system based on e-commerce. This research was a case study research with qualitative approach that aimed to analyze the marketing strategy of livestock in PT X. This research used direct interview method that was involving all respondents as many as 3 managers of PT X and 1 expert respondents. The data were analyzed using AHP (Analytical Hierarchy Process) method and presented descriptively. There are 3 interrelated elements in analyzing the marketing strategy of PT X's online livestock, including factors (delivery and product availability systems) of actors (Founder, Coordinator of Mobile Centers, and Support Service) and alternatives (maintaining product quality, expanding cooperative relationships, and improve service system).This study concluded that product availability is a priority factor with the Mobile Sentra Coordinator having the most important role as an actor in the preparation of PT X's marketing strategy. Maintaining product quality becamethe main strategy that coulds be applied by PT X in increasing its marketing.